2023
DOI: 10.1136/jitc-2023-006833
|View full text |Cite|
|
Sign up to set email alerts
|

PEOPLE (NTC03447678), a phase II trial to test pembrolizumab as first-line treatment in patients with advanced NSCLC with PD-L1 <50%: a multiomics analysis

Abstract: BackgroundChemoimmunotherapy represents the standard of care for patients with advanced non-small cell lung cancer (NSCLC) and programmed death-ligand 1 (PD-L1) <50%. Although single-agent pembrolizumab has also demonstrated some activity in this setting, no reliable biomarkers yet exist for selecting patients likely to respond to single-agent immunotherapy. The main purpose of the study was to identify potential new biomarkers associated with progression-free-survival (PFS) within a multiomics analysis.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Although predictive markers to identify clinical responders following ICI have largely focused on the T cell compartment, several recent studies have interrogated other lymphocyte populations in peripheral blood for association with clinical outcome following immunotherapy (Supplemental Table 3 ). Lo Russo et al evaluated the circulating immune profile of 65 patients with advanced NSCLC enrolled in a prospective phase II study of first line pembrolizumab prior to therapy and at the time of first radiological evaluation and found that abundance of the ratio of total natural killer cells/CD56 dim CD16 + NK cells ( p < 0.006) at baseline, and numbers of non-classical CD14 dim CD16 + monocytes ( p = 0.0039), and eosinophils (CD15 + CD16 − , p = 0.0301) after therapy correlated with favorable PFS [ 76 ]. Another study, by Xia et al, evaluated the association between patient response and baseline levels of circulating B cells in patients with NSCLC who were treated with anti-PD-1 ( n = 120) or anti-PD-L1 ( n = 30) [ 77 ].…”
Section: Circulating Immune Cellsmentioning
confidence: 99%
“…Although predictive markers to identify clinical responders following ICI have largely focused on the T cell compartment, several recent studies have interrogated other lymphocyte populations in peripheral blood for association with clinical outcome following immunotherapy (Supplemental Table 3 ). Lo Russo et al evaluated the circulating immune profile of 65 patients with advanced NSCLC enrolled in a prospective phase II study of first line pembrolizumab prior to therapy and at the time of first radiological evaluation and found that abundance of the ratio of total natural killer cells/CD56 dim CD16 + NK cells ( p < 0.006) at baseline, and numbers of non-classical CD14 dim CD16 + monocytes ( p = 0.0039), and eosinophils (CD15 + CD16 − , p = 0.0301) after therapy correlated with favorable PFS [ 76 ]. Another study, by Xia et al, evaluated the association between patient response and baseline levels of circulating B cells in patients with NSCLC who were treated with anti-PD-1 ( n = 120) or anti-PD-L1 ( n = 30) [ 77 ].…”
Section: Circulating Immune Cellsmentioning
confidence: 99%
“…These include monotherapy with immune checkpoint inhibitors (ICIs) such as pembrolizumab, as well as targeted therapy combinations with chemotherapy. The treatment regimens have spanned from specific targeted therapies, like ALK and EGFR inhibitors, to immunotherapies and their integration with chemotherapy [49,59,70].…”
Section: Findings Of the Studiesmentioning
confidence: 99%
“…Regarding the blinding of participants and personnel (performance bias), many studies were evaluated as having a high risk due to the open nature of many clinical trials, which exposes them to possible performance bias. This includes the studies by Garon et [45,[47][48][49]51,52,54,62,64,66,69,70,[73][74][75][76][77][78][79]. The concern around unblinding in open clinical trials underscores a significant issue, as both the researchers and participants are aware of the assigned treatments, potentially influencing the outcomes and adherence to treatment.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
See 2 more Smart Citations